ANALISIS PENERAPAN PENDEKATAN PEMBELAJARAN DEEP LEARNING TERHADAP KOMUNIKASI KOLABORATIF SISWA KELAS V PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI MI MUHAMMADIYAH BUNTU BARANA - Aprilla; Suparman; Saleha; Muh. Idham Haliq; Dedi Setiawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The learning process is often trapped in rote memorization (surface learning), resulting in low conceptual understanding and weak social interaction among students. The primary issue in this study is the lack of active engagement and the low quality of students' collaborative communication in understanding abstract values in Pancasila Education. This study aims to describe the implementation of the Deep Learning approach and analyze its impact on improving the collaborative communication of fifth-grade students at MI Muhammadiyah Buntu Barana. The method used is descriptive qualitative research. Data were collected through participant observation, in-depth interviews, and documentation. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The results indicate that the implementation of the Deep Learning approach through mindful, meaningful, and joyful learning elements successfully creates a profound learning atmosphere. Students do not merely memorize concepts but are able to connect them with social realities. A significant impact is observed in the improvement of collaborative communication, characterized by better listening skills, courage to express opinions, and increased group responsibility. This study implies that Deep Learning can serve as a strategic solution for educators to build democratic character and social skills in students from an early age through meaningful learning.